Optimisation of Gallic Acid and Quercetin Extraction from Phyllanthus Niruri - Suok Ling Nguang, Suok; Ling Yeong, Yi; Sook Fun Pang, Sook; Gimbun, Jolius (International Journal of Engineering and Technology, 2018)
This paper presents an optimization study of gallic acid and queretin extraction from Phyllanthis niruri by using response surface methodology. Gallic acid and quercetin was extracted with the aid of sonication and the polyphenols content was analyzed using Ultra Performance Liquid Chromatography (UPLC). The effect of extraction time, amplitude and ethanol concentration on the yield of gallic acid and quercetin were investigated. The optimum gallic acid yield (10.43 Â± 0.28 mg GA/g DW) was found in ethanol concentration of 40.0%, extraction time of 15 minutes and amplitude of 86.85% after solving the regression equation. Meanwhile, the optimum condition to obtain the highest yield of quercetin (17.48 Â± 0.21 mg Que/g DW) was found in ethanol concentration of 40.0%, extraction time of 15 minutes and amplitude of 75%. The findings in this work may serve as a useful guide to obtain highest extraction yield of gallic acid and quercetin from Phyllanthus niruri.Â Â